Revision of the genus Allocotaphis Börner, 1950 (Hemiptera, Homoptera, Aphididae, Macrosiphini) - Stekolshchikov, Andrey V.; Qiao, Ge-Xia (Zootaxa, 2023)
Allocotaphis Börner, 1950 (Hemiptera, Homoptera, Aphididae, Aphidinae, Macrosiphini) and its three species are fully revised. The history of the descriptions of the involved taxa is critically presented. Descriptions of the known morphs of these species and complete information on the biology and distribution of the species are presented. Three subjective synonymies are established: Spinaphis L.K. Ghosh, 1986 syn. n. and Longisiphoniella Chakrabarti, Saha & Mandal, 1988 syn. n. of Allocotaphis Börner, 1950, and Longisiphoniella subterranea Chakrabarti, Saha & Mandal, 1988 syn. n. of Allocotaphis multisetosa (L.K. Ghosh, 1986) comb. n. An hypothesis for the formation of the genus and the speciation that took place within it is proposed.